Pembangunan Sistem Informasi Penjualan Pada Usaha Mikro, Kecil, Dan Menengah (Studi Kasus : Pahala Fotokopi dan Digital Printing) - Martinus Maslim; Stephanie Pamela Adithama; Andreas Hemawan Tri Nugroho (Universitas Lancang Kuning, 2020)
Only a few Micro, Small and Medium Enterprises (MSMEs) in Indonesia are implementing information technology. Pahala Photocopy and Digital Printing is one of the MSMEs engaged in photocopying, digital printing, and stationery sales. The process of recording transactions is still using a manual system. Recording is still done using books and calculators as calculation tools so it consumes a lot of time, and does not guarantee the data accuracy and data security. Another problem that occurs is the lack of information obtained by business owners resulting in mistakes in decision making. The solution to the problem of Pahala Photocopy and Digital Printing is a sales information system used to record procurement, ordering photocopy and digital printing services, and stationery sales transactions. This sales information system is able to produce information needed by the owner quickly and accurately. With the implementation of this sales information system, it can improve performance and competitiveness for the Pahala Photocopy and Digital Printing.